Brain neuroplasticity related to lateral ankle ligamentous injuries: a systematic review - Maricot, A.; Dick, E.; Walravens, A.; Pluym, B.; Lathouwers, E.; De Pauw, K.; Verschueren, J.; Roelands, B.; Meeusen, R.; Tassignon, B. (Sports Medicine, 2023)
Background: Lateral ankle sprains are the most common ankle injuries in sports and have the highest recurrence rates. Almost half of the patients experiencing lateral ankle sprains develop chronic ankle instability. Patients with chronic ankle instability experience persistent ankle dysfunctions and detrimental long-term sequelae. Changes at the brain level are put forward to explain these undesirable consequences and high recurrence rates partially. However, an overview of possible brain adaptations related to lateral ankle sprains and chronic ankle instability is currently lacking. Objective: The primary purpose of this systematic review is to provide a comprehensive overview of the literature on structural and functional brain adaptations related to lateral ankle sprains and in patients with chronic ankle instability. Methods: PubMed, Web of Science, Scopus, Embase, EBSCO—SPORTDiscus and Cochrane Central Register of Controlled Trials were systematically searched until 14 December, 2022. Meta-analyses, systematic reviews and narrative reviews were excluded. Included studies investigated functional or structural brain adaptations in patients who experienced a lateral ankle sprain or with chronic ankle instability and who were at least 18 years of age. Lateral ankle sprains and chronic ankle instability were defined following the recommendation of the International Ankle Consortium. Three authors independently extracted the data. They extracted the authors` name, publication year, study design, inclusion criteria, participant characteristics, the sample size of the intervention and control groups, methods of neuroplasticity testing, as well as all means and standard deviations of primary and secondary neuroplasticity outcomes from each study. Data reported on copers were considered as part of the control group. The quality assessment tool for observational and cross-sectional studies was used for the risk of bias assessment. This study is registered on PROSPERO, number CRD42021281956. Results: Twenty articles were included, of which only one investigated individuals who experienced a lateral ankle sprain. In all studies combined, 356 patients with chronic ankle instability, 10 who experienced a lateral ankle sprain and 46 copers were included. White matter microstructure changes in the cerebellum have been related to lateral ankle sprains. Fifteen studies reported functional brain adaptations in patients with chronic ankle instability, and five articles found structural brain outcomes. Alterations in the sensorimotor network (precentral gyrus and supplementary motor area, postcentral gyrus and middle frontal gyrus) and dorsal anterior cingulate cortex were mainly found in patients with chronic ankle instability. Discussion: The included studies demonstrated structural and functional brain adaptations related to lateral ankle sprains and chronic ankle instability compared to healthy individuals or copers. These adaptations correlate with clinical outcomes (e.g. patients` self-reported function and different clinical assessments) and might contribute to the persisting dysfunctions, increased re-injury risk and long-term sequelae seen in these patients. Thus, rehabilitation programmes should integrate sensorimotor and motor control strategies to cope with neuroplasticity related to ligamentous ankle injuries.